On the Idea of a ‘Method’ in Moral Philosophy - Reichlin, Massimo (Phenomenology and Mind, 2019)
The paper discusses the two meanings that ‘method’ is often assumed to have in moral philosophy: the epistemic meaning, according to which a method is a procedure to reach moral knowledge, and the normative meaning, according to which it is a criterion of right and wrong in actions. The origin of these two, clearly connected meanings can be traced to Sidgwick’s work The Methods of Ethics. It is argued that Sidgwick’s seminal idea of a “reflective equilibrium” is a valuable and lasting contribution to the debate on moral epistemology; however, Sidgwick’s characterisation of the different normative options is biased against non consequentialist approaches by its concentration on “methods”, rather than on theories and “ultimate reasons”. This consequentialist bias still lingers in contemporary ethics.